Evaluation of Red Palm Weevils (Rhynchophorus ferrugineus: Curculionidae) for Putative Oxidation of Ingested Polystyrene and Polyurethane and Their Gut Microbiota Response - Khanchai Danmek; Pichet Praphawilai; Sampat Ghosh; Chuleui Jung; Saeed Mohamadzade Namin; Phattharawadee Aedtem; Bajaree Chuttong (Insects, 2025)
This study assessed the growth performance of red palm weevil (RPW) (Rhynchophorus ferrugineus: Curculionidae) larvae on a liquid diet of yeast-enriched potato dextrose broth (control) and on diets with added polystyrene and polyurethane. For 15 days of diet exposure, the growth and survival, plastic degradation, and gut microbiota of larvae were examined. RPWs showed higher survival rates under polystyrene and polyurethane treatments than in the control group. Head diameter showed a higher trend under polyurethane treatment than under the other treatments. Treated plastics were partly degraded after a 15-day exposure. Further analysis of plastic residues from frass revealed significant differences in Fourier Transform Infrared Spectroscopy (FTIR), with decreased intensity of characteristic peaks compared to frass from larvae fed in the control. Gut bacterial communities in the gut of RPW larvae showed that plastic feeding did not significantly alter the presence of key microbial taxa, but members of Firmicutes and Proteobacteria were higher in the plastic treatment, showing preliminary signs of plastic oxidation and degradation. Overall, these findings provide evidence that ingestion of PS and PU by RPW larvae supports their survival and alters their gut microbiota, possibly due to plastic degradation, paving the way for further research into the interactions between RPWs, their microbiome, and key functional activities, with implications for plastic waste management and recycling.